Cognitive Expansion in Narrative–Descriptive Genre: A Gender-Responsive Diagnostic Study Across High School–Vocational College Transition - Putri, Rahmadila Eka; Agustina, Mahraini; Ramadhani, Delara Putri; Chalisah, Nabilah (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
The transition from high school to vocational higher education represents a critical stage in which prior literacy knowledge shapes students’ readiness for academic and professional communication. Despite standardized EFL curricula, incoming vocational students often display uneven genre-based competence, particularly in narrative and descriptive writing. This study adopts a quantitative, diagnostic-oriented approach informed by Cognitive Diagnostic Assessment (CDA) principles to examine genre-related knowledge patterns and gender-mediated tendencies. A 30-item True/False diagnostic test, validated by two applied linguistics experts, was administered to 43 first-year students (27 females, 16 males) in the D4 English for Business and Professional Communication program at Politeknik Negeri Sriwijaya. The instrument targeted structural, linguistic, and functional attributes of narrative and descriptive texts, and data were analyzed descriptively and comparatively. Findings (RQ1) reveal uneven genre knowledge, with mean accuracy for narrative items (81%) exceeding descriptive ones (61%), reflecting differences in familiarity rather than linguistic deficiency. In addressing (RQ2), the gender-disaggregated results indicate that female students tended to excel in causal reasoning, thematic inference, and figurative interpretation, whereas males demonstrated stronger performance in factual coherence and structural precision. Regarding (RQ3), these disparities reflect cognitive diversification rather than inequality, illustrating differentiated learning pathways shaped by prior literacy exposure and gendered engagement. Although the study does not implement full psychometric CDA modeling, the diagnostic instrument provides formative insights into students’ genre cognition at a key educational transition. The findings suggest that gender-responsive, diagnostic-informed pedagogy can support equitable literacy development in vocational English contexts by leveraging complementary cognitive strengths.